EUGENIO MONTALE: TRANSLATION OF ONE POEM (Philological Studies, 2019)
This article speaks about the unique personality, the famous Italian poet – E. Montale. E. Montale could create his own poetic language. The poet’s work is becoming more relevant in Italy and in the others countries, but it is remaining not enough famous and assessed in the modern Russia. Many specialists translated the poems of E. Montale in Russian language. The author of this paper examines peculiarity of his work, of personal style, analyses different tendencies, that are typical for the translations of the poem of E. Montale. This article offers the author’s translation of his poem “Meriggiare pallido e assorto”, that is fulfilled by the author in co-authorship with G. Belussi.
Keywords: Italian poetry, individual style, intonation, cultural tradition, translation, poetic language, rhyme